TWO FABLES OF BOOKKEEPING. - Littleton, A. C. (The Accounting Review, 1927)
Abstract This article presents two fables to illustrate some principles of accounting. A natural series of events described in one fable put into the hands of a character, called T, the characteristic elements of real double-entry book- keeping. This man, intelligent and observant by hypothesis, could not have been long in finding out that every transaction gave rise to a double recording, that every sum written in the debit of one of the two accounts figured also in the credit of the other, and that as a consequence, the total of the debits were equal to the total of the credits, and finally, that the debit balance of one of the two accounts was in reality, and of necessity, equal to the credit balance of the other. The principles of double-entry were thus clearly formulated at first without the men who conceived them comprehending their significance. The other fable tells that there was in the old Roman law, a very definite procedure of contracting a binding debt and a set form of preliminary conversation. There was an equally definite procedure for transferring a debt to a third party.